Teologi Penatalayanan dalam Pemberdayaan Jemaat untuk Penguatan Partisipasi Finansial Gereja - Jeffry Cartouche Laseduw; Yonatan Alex Arifianto; Reni Triposa (STTI Harvest Semarang, 2026)
Church fundraising is an important aspect in supporting the sustainability of ministry and spiritual mission, but it often faces challenges in the form of suboptimal congregational participation, a lack of congregational understanding of spiritual responsibility, and limited management strategies that are integrated with congregational empowerment. Amidst developments in technology and Christian education, churches are required to develop approaches that are not only administrative in nature, but also build awareness, motivation, and commitment among congregations as a whole. This study aims to analyse the congregation empowerment model as the foundation for church fundraising. The research method used is descriptive qualitative with a case study approach and analysis of theological literature and church practices. The results show that congregation empowerment based on Christian education and the development of individual gifts increases the congregation's spiritual involvement and awareness. The integration of technology can maximise programme personalisation, while community-based collaborative strategies strengthen participation and the sustainability of church services. Thus, congregation empowerment becomes an essential foundation for the effectiveness of sustainable and spiritually meaningful fundraising. AbstrakPengumpulan dana gereja merupakan aspek penting dalam mendukung keberlanjutan pelayanan dan misi spiritual, namun seringkali menghadapi tantangan berupa partisipasi jemaat yang belum optimal, kurangnya pemahaman jemaat mengenai tanggung jawab rohani, serta keterbatasan strategi pengelolaan yang terintegrasi dengan pemberdayaan jemaat. Di tengah perkembangan teknologi dan pendidikan Kristen, gereja dituntut untuk mengembangkan pendekatan yang tidak hanya bersifat administratif, tetapi juga membangun kesadaran, motivasi, dan komitmen jemaat secara menyeluruh. Penelitian ini bertujuan untuk menganalisis model pemberdayaan jemaat sebagai fondasi pengumpulan dana gereja. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kasus dan analisis literatur teologis serta praktik gerejawi. Hasil penelitian menunjukkan bahwa pemberdayaan jemaat berbasis pendidikan Kristen dan pengembangan karunia individu meningkatkan keterlibatan dan kesadaran spiritual jemaat. Integrasi teknologi dapat memaksimalkan personalisasi program, sementara strategi kolaboratif berbasis komunitas memperkuat partisipasi serta keberlanjutan pelayanan gereja. Dengan demikian, pemberdayaan jemaat menjadi fondasi esensial bagi efektivitas pengumpulan dana yang berkelanjutan dan bermakna secara spiritual.